6y+4-2y=32-3y

Simple and best practice solution for 6y+4-2y=32-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+4-2y=32-3y equation:


Simplifying
6y + 4 + -2y = 32 + -3y

Reorder the terms:
4 + 6y + -2y = 32 + -3y

Combine like terms: 6y + -2y = 4y
4 + 4y = 32 + -3y

Solving
4 + 4y = 32 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
4 + 4y + 3y = 32 + -3y + 3y

Combine like terms: 4y + 3y = 7y
4 + 7y = 32 + -3y + 3y

Combine like terms: -3y + 3y = 0
4 + 7y = 32 + 0
4 + 7y = 32

Add '-4' to each side of the equation.
4 + -4 + 7y = 32 + -4

Combine like terms: 4 + -4 = 0
0 + 7y = 32 + -4
7y = 32 + -4

Combine like terms: 32 + -4 = 28
7y = 28

Divide each side by '7'.
y = 4

Simplifying
y = 4

See similar equations:

| 6(-4m+5)=-114 | | 4(4x-2)=50 | | 3x+6y=24forx | | 10x+4x+12=360 | | 7x-5=2x+17 | | 3(y-1)-(y+2)=7 | | x-3+4=-6 | | Y=-5k^2+65k-150 | | 5y^2-1+2(y^2+2)= | | 3x+9=-63-9 | | 3-7(-6p+3)=-p+9 | | -(2y+1)=8(y+2)+2 | | 0.70x+0.30(360-x)=0.60(100) | | 4z+6.1= | | 0.2d-1.2=0.4d+2 | | 5x-2x+9=45-9x | | 4cos^2(x)+8cos(x)-5=0 | | 4+10h=8h+12 | | 18x+-1(8x+-7)=67 | | 188x-(8x-7)=67 | | sin(45-x)=0 | | 2x+X+2x+x=180 | | 2Y+3=6Y-7 | | Y=a^2-8a+15 | | 0.35x+0.40(4)=0.39(x+4) | | 2(x-5)=(5-x) | | 2x^4-x^2-216=0 | | -4(k+3)=6-2k | | 12w=-4 | | 0.2t=0.9t+0.4t | | 11a+18=-2+9a | | 6-(3z-2)=3-4z |

Equations solver categories